Budaya Tri Hita Karana Memoderasi Pengaruh Whistleblowing System Terhadap Pencegahan Fraud Pada LPD Di Kecamatan Sukawati - Yustina, Ni Wayan Ariska; Hutnaleontina, Putu Nuniek (Hita Akuntansi dan Keuangan, 2025)
LPD is a traditional community institution that only exists in Bali, making this financial institution unique because its management is imbued with the spirit of Hindu customary law and culture, so its existence should be maintained. The number of cases of fraud (fraud) against LPD funds makes the need for better management to prevent the occurrence of such fraud. The purpose of this study was to investigate the effect of the whistleblowing system on fraud prevention moderated by the Tri Hita Karana culture at LPDs in Sukawati District. The population used in this study were all LPD employees in Sukawati District who were registered at LPLPD Gianyar as many as 138 people, using the saturated sample technique, so that the entire population was sampled because all employees at the LPD had the potential to commit or see fraud research sample. Data were analyzed using PLS Moderation analysis. The results of the analysis show that the whistleblowing system has a positive and significant effect on fraud prevention at LPDs in Sukawati District. The Tri Hita Karana culture is able to moderate (strengthen) the relationship between the whistleblowing system and fraud prevention at LPDs in Sukawati District. It is recommended that the LPD in Sukawati District be able to provide good protection, maintain the confidentiality of the reporter's identity, so that every employee who knows fraudulent acts can report and have a sense of security when carrying out these reporting actions.